A guide to cruising Northern Australia : anchorages Darwin to Carnarvon - Richards, Leslie P. (Malak, N.T. : Adventure Yarns, 2007)
"A Guide to Cruising Northern Australia - Darwin to Carnarvon is a sailing guide to anchorages which may be found between Darwin in the Northern Territory of Australia, westerly around the Joseph Bonaparte Gulf and the Kimberley Coast to Carnarvon in Western Australia."--Provided by publisher.
Keywords: Sailing -- Northern Territory; Sailing -- Western Australia; Boats and boating -- Northern Territory; Boats and boating -- Western Australia